Synthesis and characterization of nanostructured undoped and Sn-doped ZnO thin films via sol-gel approach - Aydin, H.; El-Nasser, H. M.; Aydin, C.; Al-Ghamdi, Ahmed. A.; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2015)
Thin films of Sn-doped ZnO were prepared via facile sol gel spin coating method. The structural and optical properties of the films were investigated by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM), and UV-VIS-NIR spectrophotometer. The X-ray results confirmed that all the ZnO thin films are polycrystalline with a hexagonal wurtzite structure with a preferential orientation of (002) plane. The crystallite size and lattice parameter values of the films were obtained. Atomic force microscopy results indicate that the Sn-doped ZnO films have the nanostructure. The grain size values of the films were found to vary from 39.23 to 71.84 nm with Sn doping. The nanostructure of the Sn-doped ZnO films was also confirmed by scanning electron microcopy. The optical bandgaps of the films were calculated for the various Sn contents. The refractive index dispersion curves obey the single oscillator model. The optical constants and dispersion parameters of the ZnO films were changed with Sn doping. The obtained results suggest that the structural and optical properties of ZnO films can be controlled by Sn doping. (C) 2015 Elsevier B.V. All rights reserved.
Conference and Exhibition on Science and Applications of Thin Films (SATF) -- SEP 15-19, 2014 -- Cesme, TURKEY
Keywords: Sn-doped ZnO; Nanoparticles; Sol-gel; Thin films; Microstructure; Optical properties